Prevalence and risk factors associated with high somatic cell count in Chinese dairy herds - Deng, Zhaoju; Wang, Kun; Xu, Chuang; Cao, Jie; Ma, Chong (Frontiers in Veterinary Science, 2022)
This study aimed to (1) estimate the prevalence of cow-level high somatic cell count (SCC) in Chinese dairy herds and (2) identify potential factors associated with cow- and herd-level SCC variables. The monthly data of dairy herd improvement from a total of 131 dairy herds in 11 provinces during 2019 were collected. Mixed models were constructed using the cow composite milk SCC and variance of cow SCC as dependent variable separately, parity, season, days in milk (DIM), herd size, and farm type (family-owned vs company-owned) as fixed effect and accounting for nested random herd and cow effect. Herd-level SCC-related variables, namely the monthly proportion of high SCC, monthly proportion of new high SCC, monthly proportion of chronic high SCC, and monthly proportion of new chronic high SCC were used as dependent variables separately against season, herd size, and farm type using negative binomial regression with random herd effect. The overall average prevalence of high SCC for each month per farm was 0.26 (2.5%-97.5% quantile: 0-0.56). Company-owned farms generally performed better in herd SCC management. Seasons were significantly associated with all of these variables, summer and autumn were the seasons associated with worse situation in herd SCC. This study is the first to assess the high SCC in a large number of Chinese dairy herds, which is useful for farms to tailor on-farm mastitis control programs in China.